Spirituality, spiritual need, and spiritual care in aged care: What the literature says - Jackson, David (Journal of religion, spirituality & aging, 2016)
This article addressed the following questions: How are spirituality, spiritual need, and spiritual care in aged care defined? What constitutes spiritual care for older people in aged care? From an organisational perspective, what are barriers and enablers to providing spiritual care? Spirituality and spiritual care were defined in a variety of ways in the literature. The literature endorsed nurses and other aged care staff engaging in elements of spiritual care of older people as valuable. A whole-of-organisation approach is required rather than leaving it to the individual. New guidelines are being developed specifically for spiritual care in aged care.